2022
DOI: 10.7759/cureus.29394
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Longitudinal Adolescent Transition of Care Curriculum: Identifying Comfort and Barriers Among Residents

Abstract: Amid growing recognition of the importance of transitioning adolescents and young adults (AYA) from pediatric-to adult-oriented health care systems, residency programs are being tasked with educating residents on best transition practices. However, consensus on how to approach training residents in transition of care (TOC) is limited. Our academic residency program therefore created and implemented a TOC of AYA curriculum for pediatric residents in an effort to increase provider knowledge and comfort with this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Moreover, there is variability in the transition process between institutions and clinics [ 20 - 21 ]. Residency curricula incorporating transition of care knowledge and skills have been shown to be effective at single institutions [ 22 - 25 ]. This study showed that a standardized resident-led transition of care curriculum is effective at two institutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is variability in the transition process between institutions and clinics [ 20 - 21 ]. Residency curricula incorporating transition of care knowledge and skills have been shown to be effective at single institutions [ 22 - 25 ]. This study showed that a standardized resident-led transition of care curriculum is effective at two institutions.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that residents in alternating clinics are less likely to have supervising faculty familiar with transition of care processes, therefore baseline knowledge prior to this curriculum was lower, allowing for greater knowledge gain. Most curricula and studies focus on patients with special healthcare needs [ 8 , 12 , 20 - 21 , 23 , 26 ], occur at single institutions/clinics [ 23 , 25 , 27 - 28 ], or evaluate transition goals for resident education as opposed to implementation [ 17 , 29 - 30 ]. This pilot curriculum executes transition education for residents caring for patients with and without special health care needs in the outpatient setting and to our knowledge, is the first resident-level transition curriculum conducted at multiple institutions.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this scoping review suggest that care providers must stay up-to-date with transition-related education in order to provide adequate transitional support. Studies interviewing paediatric residents and specialists found that providers experienced low knowledge and comfort levels with transitions from paediatric to adult care due to a gap in the provision of structured curriculum 97 98. This finding is unsurprising given one-third of undergraduate/graduate medical education programmes fail to provide instruction about transition of care 99.…”
Section: Discussionmentioning
confidence: 99%